Naturezas-mortas sobreviventes: uma análise sobre as imagens contemporâneas - Corrêa, Milena Regina Duarte (2024)
This Doctoral Thesis in Visual Arts discusses the survival of still lifes in contemporary art. The study aims to analyze the life of recent images from the perspective of the adaptations and expansions that occur in this hybrid and conceptual universe, as reverberations of previous times in the history of art. Instigated by theoretical questions revitalized by Georges Didi-Huberman (1953), we identify aspects of form and content that are repeated in contemporary images; we also verify a phenomenon present in the critical fortune of his conceptual predecessor, Aby Warburg (1866 - 1929), when he theorized the Nachleben. This text therefore draws up an association between images, based on contemporary works of art, with the aim of investigating and discussing the effects that survive from one era to the next and, above all, the conceptual innovations of today's productions. In this way, the investigation contributes to research in Art History, Theory and Criticism, in terms of expanding knowledge about still lifes, beyond the historiographical limits of the genre. With regard to contemporary still lifes, the notion of anachronistic survival is explored, through the unexpected returns present in these complex and subversive images.